THE GERMINATION OF TRANSLANGUAGING: IN AND OUTSIDE THE SCHOOL CONTEXT - Serai, Safia (PEOPLE: International Journal of Social Sciences, 2019)
In 1994, the term translanguaging emerged in the Welsh secondary schools. Its first use is attributed to Cen Williams who referred to this pedagogical practice as receiving the input in one language and producing in a different one. Translated later by Colin Baker, translanguaging has been extended to the scholarly literature to entrench, and become part of various educational and social domains. Pedagogical translanguaging is the name given to the language practice that takes place in the classroom context, while non-pedagogical translanguaging is the umbrella term for the bilinguals’ practices inside and outside the educational settings. Though the word translanguaging is frequently used in the literature, there is no exact definition to it, so the interest in this current language practice resulted in many definitions. This paper begins by reviewing the origins of translanguaging as well as its development from educational settings to outside the classroom then returning to the school. Furthermore, as translanguaging is controversial, the discrepancy between translanguaging and the different teaching and learning approaches and methods will be scrutinised to make a distinction between translanguaging and the use of the students’ home language. This can be better understood by explaining the notion of approach and how such a language practice can fall under the name of a teaching approach.